县域经济发展策略研究 = Study on the development strategy for regional economy - 李军 Li, Jun (2008)
It is urgent to accelerate the development of county economy in order to face the ever-sharpening market competition. In this thesis, the general rule and the problems of the county economy have been investigated on the basis of theoretical and practical analysis. The development strategy of county economy has been proposed.